Analysis of Spatial-Temporal Sampling and Equal Distance Parallel Formation Control of Unmanned Surface Bathymetric Vehicle. (5th July 2013) - Jin, Jiucai; Zhang, Jie; Guan, Sheng; Ma, Yi
Analysis of the spatial-temporal sampling of Unmanned Surface Bathymetric Vehicles (USBV) is vital for depth measurement performance, which is the basis for optimum sampling of multi-USBV cooperative parallel formations. This paper's ultimate goal is to find the optimum sampling style of multi-USBV parallel formations and to design the corresponding control law. First, the relationship between spatial-temporal sampling intervals and measurement performance is examined using the Objective Analysis method, giving an illustrative example of the sampling of two USBVs. Second, three types of spatial-temporal constraint are defined and the type of USBV is analysed, which is spatially constrained. Lastly, according to the spatially constrained USBV type, the control law for multi-USBV equal-distance parallel formations with spatial synchrony is designed based on self-propelled particles theory, which is validated in the simulations based on the USBV dynamic model.